2000
DOI: 10.1002/(sici)1097-4644(2000)77:34+<61::aid-jcb11>3.3.co;2-j
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of genes by tumor cells of a low or a high malignancy phenotype: The case of murine and human Ly-6 proteins

Abstract: Progression of tumor cells toward a high malignancy phenotype and metastasis is a multi‐event cascade involving inter alia alterations in the expression of various genes. The focus of our laboratory is on genes whose altered expression may lead, directly or indirectly, to an increased malignancy phenotype. The identification of such genes and the evaluation of the consequences of their altered expression is essential for attempts to halt tumor progression and prevent metastasis formation. Published work origin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 14 publications
0
8
0
Order By: Relevance
“…PSCA is located on chromosome 8q24.2 and encodes a cell surface glycoprotein PSCA, which belongs to the Ly‐6/Thy‐1 family of glycosylphosphatidylinositol anchored surface protein 18. Although the definitive function of PSCA has not been clarified either in normal cellular processes or tumorigenesis, proteins in the Ly‐6 family have been reported to be associated with tumorigenesis and tumor cell adhesion 19, 20. The Thy‐1 family has versatile functions in cell adhesion, proliferation, survival, and cytokine/growth factor responses 21.…”
Section: Discussionmentioning
confidence: 99%
“…PSCA is located on chromosome 8q24.2 and encodes a cell surface glycoprotein PSCA, which belongs to the Ly‐6/Thy‐1 family of glycosylphosphatidylinositol anchored surface protein 18. Although the definitive function of PSCA has not been clarified either in normal cellular processes or tumorigenesis, proteins in the Ly‐6 family have been reported to be associated with tumorigenesis and tumor cell adhesion 19, 20. The Thy‐1 family has versatile functions in cell adhesion, proliferation, survival, and cytokine/growth factor responses 21.…”
Section: Discussionmentioning
confidence: 99%
“…It is shown that PSCA, like other GPI-anchored proteins, is involved in the survival of stem cells, in T-cell activation and proliferation, and in cytokine and growth factor responses (97, 98). Furthermore, several studies have connected the Ly-6 family of PSCA-like GPI-anchored proteins to tumor growth and metastazation (99102). …”
Section: Prostate Cancer Antigensmentioning
confidence: 99%
“…Additionally, proteins in the Thy-1 family have been reported to function in T cell activation and proliferation, stem cell survival, and cytokine and growth factor responses [10]. Furthermore, the family of Ly-6 genes has been associated with carcinogenesis [11, 12], cellular activation [13] and cell adhesion of tumor cells [14]. While these studies point to potential roles of PSCA, no definitive function has been attributed to the protein either in normal cellular processes or abnormal tumorigenesis.…”
Section: Prostate Stem Cell Antigenmentioning
confidence: 99%